Hu-lu-su-pian ameliorates hepatic steatosis by regulating CIDEA expression in AKT-driven MASLD mice - Ren, Rumeng; Wang, Qi; Deng, Dongjie; Guo, Aoao; Chen, Xin; Meng, Yan; Fang, Ying; Zheng, Guohua; Xu, Zhong; Li, Man; Hu, Junjie (Frontiers in Pharmacology, 2025)
IntroductionHu-lu-su-pian (HLSP) is an oral tablet derived from the active compounds of Cucumis melo L., a traditional Chinese medicine. This contemporary formulation is frequently employed in clinical settings for the management of liver ailments. However, the molecular mechanism by which HLSP affects metabolic dysfunction-associated steatotic liver disease (MASLD) remains unclear. This study aimed to explore the therapeutic potential of HLSP on MASLD and the underlying mechanism.MethodsThe researchers used ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS) to identify the primary chemical components of HLSP. A mouse model of MASLD induced by AKT was established through hydrodynamic transfection with activated forms of AKT. Serum biochemical indices and liver pathological assessments were employed to evaluate the pharmacodynamic effects of HLSP on MASLD. Transcriptomic analysis of the liver was conducted to detect differentially expressed genes (DEGs). Further examination of significant DEGs and proteins was performed using quantitative real-time polymerase chain reaction (RT-qPCR), Western blotting, and immunohistochemistry (IHC) techniques, respectively. The efficacy and molecular mechanisms of HLSP in MASLD were further explored in HepG2 and Huh-7 cells in the presence of gene overexpression.ResultsFrom the UPLC-Q-TOF-MS/MS results, we detected fifteen components from HLSP. From the results of serum biochemical indices and hepatic pathology analyses, it is clear that HLSP is effective in treating MASLD. The findings from hepatic transcription studies revealed CIDEA as an essential DEG that facilitates lipid droplet (LD) fusion and enhances de novo fatty acid synthesis from scratch in cases of hepatic steatosis, which HLSP has the potential to counteract. In addition, HLSP significantly reduced lipid accumulation and expression of critical genes for de novo fatty acid synthesis in HepG2 and Huh-7 cells overexpressing CIDEA.DiscussionThe present study preliminarily suggests that HLSP can ameliorate hepatic steatosis by inhibiting CIDEA-mediated de novo fatty acid synthesis and LD formation, which may offer a potential strategy for treating MASLD.